Research on the possibility of improving the properties of roads aggregate and local by waste materials (nylon bags and plastic bottles) - حنا رامي (Latakia University Journal -Engineering Sciences Series, 2023)
Roads need large quantities of gravel to build, and the stones that meet the technical specifications are rare, and on the contrary, weak stones are spread geotechnics in abundance, which necessitates their use, but after improving their properties. In the works of the foundation layer and under the foundation) and improving local soils from the excavation product or located in the place of construction of transportation roads. In our research, different percentages of nylon (nylon bags and plastic bottles for filling fresh water) were added to the structurally weak pebbles (weak wear resistance) and we got a noticeable increase in the wear resistance (Los Angeles), so the wear value decreased to 32%, while before the addition it was no Less than 44%, which increases the durability of the stones and their resistance to loads and weather factors. When adding nylon and plastic scraps to the local soil, its bearing capacity increased by up to 100%, reaching a value of 46% when adding 3% by weight of nylon scraps and plastic package clippings.